The Political Forest in the Era of Green Neoliberalism. Issue 4 (27th April 2020) - Devine, Jennifer A.; Baca, Jenny A.
Abstract: Nancy Peluso and Peter Vandergeest first used the term "political forest" to denaturalise forests, refiguring them as political ‐ecological entities. Across three moments of colonialism, post‐colonial independence, and counter‐insurgency struggles, they analyse how states in Southeast Asia (re)made forests as a means of territorialising power. More recently, they identify a fourth, contemporary moment characterised by the entry of diverse non‐state actors into the making of forests, and a shift in the rationalities and technologies of forest management. We label this fourth moment "green neoliberalism" to identify an era of global environmental governance characterised by market‐based solutions to socio‐ecological problems, biodiversity conservation and carbon sequestration priorities, and new moral and scientific claims to forests spanning a variety of sites and scales. The papers in this symposium transport the analytic of the political forest to Colombia, the Democratic Republic of Congo, Guatemala, Indonesia, Madagascar, Singapore, and Thailand to examine how green neoliberalism's discourses and practices have created new sites and expressions of territorialisation, governance, knowledge production, and subject formation. In doing so, they illuminate the multiplicity of actors (re)making political forests at a moment when forests' virtues as carbon sinks and biodiversity hotspots draw massive flows of capital and justify remaking socio‐ecological relations across the globe.